2022
DOI: 10.3389/fimmu.2022.966364
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of FOXP3 expression by the AP-1 family transcription factor BATF3 requires partnering with IRF4

Abstract: FOXP3 is the lineage-defining transcription factor for Tregs, a cell type critical to immune tolerance, but the mechanisms that control FOXP3 expression in Tregs remain incompletely defined, particularly as it relates to signals downstream of TCR and CD28 signaling. Herein, we studied the role of IRF4 and BATF3, two transcription factors upregulated upon T cell activation, to the conversion of conventional CD4+ T cells to FOXP3+ T cells (iTregs) in vitro. We found that IRF4 must partner with BATF3 to bind to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Previous studies have shown that metabolic pathways are 'rewired' upon activation and differentiation of resting lymphocytes shifting from oxidative phosphorylation to aerobic glycolysis fulfilling the bioenergetic demands during proliferation, differentiation and the biosynthesis of precursors 19 . IRF4-driven metabolic switch towards glycolysis has been demonstrated before for CD8 + T 20 and Treg cells 9 , which is in line with our data. Distinct metabolic programs have also been associated with the polarization along the Th17 cell and Treg cell axis and oxidative phosphorylation has been correlated with a Treg cell phenotype 21 .…”
Section: Irf4 Transcriptionally Regulates Distinct Effector Functions...supporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that metabolic pathways are 'rewired' upon activation and differentiation of resting lymphocytes shifting from oxidative phosphorylation to aerobic glycolysis fulfilling the bioenergetic demands during proliferation, differentiation and the biosynthesis of precursors 19 . IRF4-driven metabolic switch towards glycolysis has been demonstrated before for CD8 + T 20 and Treg cells 9 , which is in line with our data. Distinct metabolic programs have also been associated with the polarization along the Th17 cell and Treg cell axis and oxidative phosphorylation has been correlated with a Treg cell phenotype 21 .…”
Section: Irf4 Transcriptionally Regulates Distinct Effector Functions...supporting
confidence: 93%
“…In Treg cells, IRF4, in concert with BATF3, regulates the expression of the lineage-specific TF FOXP3 and hence controls (i)Treg induction 9 . Despite its repressive function on FOXP3 expression, IRF4 acts as a downstream target of FOXP3 and is required for the development of fully functional Treg cells and their immunomodulatory activity in a cellular context 6,9 . In a complex, IRF4 and FOXP3 control the expression of gene loci 5 associated with Treg cell suppressive properties, e.g., Il10 and Icos 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Arnold PR. et al demonstrate that BATF3, a TF of AP-1 family, partnering with IRF4 to repress FOXP3, and so Treg production (40). On the opposite, both IRF4 and BRDM1 are correlated with CTLA4, a Treg marker, and with SOCS3, a regulator of STAT3 and downregulated in CCC.…”
Section: Discussionmentioning
confidence: 99%
“…Foxp3 is a lineage-defining TF for Tregs and the key regulator of its development and function ( 52 , 53 ). IRF4, which acts downstream of Foxp3, can physically and functionally interact with Foxp3 and cooperate with BATF3 to regulate Foxp3 expression ( 54 , 55 ), which instructs effector Treg cell differentiation and immune suppression ( 56 ). Moreover, Blimp1 is a target of Foxp3 in Treg cells, and it is directly induced by IRF4 ( 57 , 58 ).…”
Section: Roles Of Irf4 In the Differentiation And Function Of Cd4+ T ...mentioning
confidence: 99%